1986
DOI: 10.1070/qe1986v016n01abeh005188
|View full text |Cite
|
Sign up to set email alerts
|

Efficiency of ionic lasers with energy transfer from a buffer gas

Abstract: We propose two approaches for determining the native basins in off-lattice models of proteins. The first of them is based on exploring the saddle points on selected trajectories emerging from the native state. In the second approach, the basin size can be determined by monitoring random distortions in the shape of the protein around the native state. Both techniques yield similar results. As a byproduct, a simple method to determine the folding temperature is obtained.Chains of beads on cubic or square lattice… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1998
1998
2014
2014

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 2 publications
0
4
0
Order By: Relevance
“…It is obvious that the CDS works as an external ionizer for the NG plasma and thus that processes in the CDS are weakly connected to the NG parameters. This explains why the optimum density of metal atoms (Vainer et al 1979) and, as a result, the efficiency of pumping (Vainer et al 1986) inside the NG of a HCD are higher than those in a PC. Thus, the scenario of generation of high-speed electrons determines the sort of EDF which differs considerably from the Maxwellian distribution due to these being a large amount of highspeed electrons (Kagan et al 1972a(Kagan et al , 1972b(Kagan et al , 1973(Kagan et al , 1975a(Kagan et al , 1975b.…”
Section: Introductionmentioning
confidence: 99%
“…It is obvious that the CDS works as an external ionizer for the NG plasma and thus that processes in the CDS are weakly connected to the NG parameters. This explains why the optimum density of metal atoms (Vainer et al 1979) and, as a result, the efficiency of pumping (Vainer et al 1986) inside the NG of a HCD are higher than those in a PC. Thus, the scenario of generation of high-speed electrons determines the sort of EDF which differs considerably from the Maxwellian distribution due to these being a large amount of highspeed electrons (Kagan et al 1972a(Kagan et al , 1972b(Kagan et al , 1973(Kagan et al , 1975a(Kagan et al , 1975b.…”
Section: Introductionmentioning
confidence: 99%
“…As a result of the prediction of energy parameters of lasers emitting on new transitions it is shown that these lasers may become effective sources of radiation not only in visible but also in the infrared. 10 -9 10 -11 10 16 10 14 10 12 10 10 10 13 10 11 10 15 10 -10 for the following levels of thallium ion: 7 3 P 2 (curve 1), 7 3 P 1 (2), 7 3 P 0 (3), 6 3 D 3 (4), 6 3 D 2 (5) and 6 3 D 1 (6); (b) the dependences of the gain for the IR transitions: 7 3 P 2 -6 3 D 3 (curve 1), 7 3 P 1 -6 3 D 2 (2) and 7 3 P 0 -6 3 D 1 (3). …”
Section: Results Of Numerical Simulation and Dynamics Of Population Imentioning
confidence: 99%
“…The values of specific laser output power were found using the calculations of the energy conver sion efficiency η of discharge to output energy of laser radiation in HCD and experimental data on the specific input power entered to the discharge at the optimum value of current density j opt for each of the laser transition: (11) where is the quantum efficiency, is the pumping efficiency, i.e. serial conver sion of the discharge energy (power) into the energy of fast electrons of the NG plasma, further into the energy accumulated in ions (in atoms B m ) and transferred to metal atoms in the CT (or PI) reaction; η las -the conversion efficiency of energy which has been accumulated in excited ions of metal M + *, into laser light.…”
Section: Laser Output Powermentioning
confidence: 99%
See 1 more Smart Citation